2020
DOI: 10.18231/j.jooo.2020.042
|View full text |Cite
|
Sign up to set email alerts
|

Morphometric analysis of lingual foramen on CBCT: A retrospective radiographic study

Abstract: Lingual foramen is an opening present commonly on the lingual aspects of mandible and it is commonly a midline structure. It consists of blood vessels that supply the anterior mandible. This study was conducted with aim of analyzing the location, number, radiographic subtypes and relationship of lingual foramen/foramina with the alveolar crest on Cone Beam Computed Tomography. Double lingual foramen is shown in most of the cases followed by single foramen. In our study, all 104(100%) patients showed median and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 6 publications
1
3
1
Order By: Relevance
“…The occurrence of FSS ranged from 62.0% to 86.8%, while the prevalence of FIS ranged from 13.0% to 83.8%. The differences reflected the different characteristics and populations studied, which included populations from several countries [2,8,13]. The difference between our results and those of other authors may have been because the Brazilian population has a greater miscegenation rate and because our sample was much larger than the sample of other studies.…”
Section: Discussioncontrasting
confidence: 79%
See 2 more Smart Citations
“…The occurrence of FSS ranged from 62.0% to 86.8%, while the prevalence of FIS ranged from 13.0% to 83.8%. The differences reflected the different characteristics and populations studied, which included populations from several countries [2,8,13]. The difference between our results and those of other authors may have been because the Brazilian population has a greater miscegenation rate and because our sample was much larger than the sample of other studies.…”
Section: Discussioncontrasting
confidence: 79%
“…Furthermore, for the FIS analyses, most studies did not consider the foramen in other positions as this study did. However, the identification of at least one lingual foramen in the midline of the mandible was possible in most analyses [1,7,8,13].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our present study the number of lingual canals ranged from one to six canals, with 5,34,37,23,7,16,19 as their studies had similarly reported at least one lingual foramen in 100% of the examined cases. Approaching almost similar results, De Andrade Santos et.…”
Section: Number Of Lingual Foraminasupporting
confidence: 53%
“…al. 202119 (5.77%). While the least prevalent number detected in males was six lingual canals (2.9%) similar to Wang et.…”
mentioning
confidence: 99%